Kontrasepsi Menurut Pandangan Gereja Katolik dan Implementasinya Bagi Kehidupan Berkeluarga Masa Kini - Yanto Sandy Tjang; Noverin Andrea Anang; Joyce Anggraeni; Mayong Andreas Acin (STP St. Bonaventura Medan, 2025)
This study aims to investigate the Catholic Church’s view on the morality of artificial contraception through magisterial teachings and its implications for contemporary family life. Using a qualitative approach and literature study method, this research analyzes official Church documents such as Casti Connubii, Humanae Vitae, Familiaris Consortio, Amoris Laetitia, and the Catechism of the Catholic Church, as well as academic literature and international survey reports that illustrate the perspectives of the faithful regarding contraception. Content analysis is conducted through data reduction, presentation of findings, and conclusion drawing to identify theological and pastoral themes related to the morality of contraception. The results reveal a significant discrepancy between the Church’s teachings which consistently reject artificial contraception for separating the unitive and procreative meanings of sexual relations, and the practices of many Catholics who tend to view contraception as a morally acceptable option within contemporary medical, social, and economic contexts. In conclusion, although the Church proposes Natural Family Planning methods as an alternative aligned with natural law, the gap between doctrine and lived reality requires a more dialogical, educational, and compassionate pastoral approach so that Church teaching remains relevant and meaningful in the lives of Catholic families today.